Redes sociais digitais como elemento de inovação para a comercialização de produtos na área cosmética - Moreira, Aline (2021)
Digital social networks are not only an entertainment space, because many enterprises look at this place as a valuable entrepreneurship source. Thus, the platform Instagram® became one of the most important ways of digital trade; it allows diverse ways of communication and interaction between stakeholders, besides distinct expositions of products and services. At the social networks, the interactions permit that different actors cooperate with companies in many spontaneous aspects. Furthermore, it is possible to do satisfactory researches or innovation with followers from different companies, including the cosmetic field. Innovation is the success key of the cosmetic sector, because it proposes satisfaction and loyalty to customers, once the goods life cycle has considered short. This research had as the main goal to verify the contributions of ties into the innovative mode of digital enterprises from the cosmetic sector, which sell their products at the social network Instagram®. First, it was done a bibliographic review, covered through the Social Networks Theory, emphasizing the ties exposed by Mark Granovetter, besides the literature related to innovation, its forms and sources on the organizational field. After that, it was exposed the used methodology, which is characterized as qualitative, developed through multiple case studies, made with 12 enterprises on the national level. Thus, the analysis and results were shown. Among the main results, it was understood that ties were established through the investigated platform to help the organizations substantially, once through the information extraction from Instagram® they improve and/or develop new dealing formulas with needs and demand from the target public. Beyond, the ties made by social network referred help with implementation tactics related to marketing, as the communication strategies with costumers and followers. The connections identified among the actors contribute to the expansion and improvement of organizational actions. Therefore, Instagram® develops the essential role to approximate the stakeholders from enterprises; it allows informal interactions, which straight help the innovations developed through organizations by ties established at the platform. Innovation is essential to get the sector competitivity because through it there is distinction from companies, which produces and/or sells similar products. It also proposes new tendencies and allows that many enterprises start activities through it. Thus, the investigated companies attest to a lot of challenges when market products at the social network, like keep a satisfying virtual store window, until making innovation in a space where everybody does the same. However, the biggest challenge is to cover the target public, doing that the publications get the bigger users number, without necessarily pay for all publications made by the companies.